The Role of Political Institutions of Emerging Multinational Economies’ Cross-Border Mergers and Acquisitions in the OECD Countries - Wu, Yaoan; Qu, Yi; Wen, Guowang; Bao, Jiatong (Asian Development Policy Review, 2022)
Cross-border mergers and acquisitions (CBMAs) have experienced a phenomenal growth. This is partly fueled by the continued development of multinational enterprises (MNEs) in developed economies (DEs). This empirical study investigates the role of political institutions in location choice regarding CBMAs in the emerging multinational economies (EMNEs) of OECD countries. Using the six-dimension framework of WGI indicators, we examine the relationship between the political environment in the host/home countries and EMNEs’ CBMAs in the organization of economic co-operation and development in OECD countries. The empirical results indicate that EMNEs escape tight political control and weak regulatory framework in the home country compared to DEs. Violent and unstable investment environments impede domestic development, and more exporting activities occur. The results confirm that emerging economies (EEs) should improve the quality of institutions to increase outward CBMAs. Meanwhile, DEs should make full use of open and market-friendly policies to attract more inward CBMAs.